Maquinices: esculturas irônicas - Silva, Andre Marcos da Silva (2017)
The dissertation proposes the process of construction of Maquinices: ironic sculptures, with an ironic relation to how much we are involved in this human-machine context, in this way, through contemporary art the creation of devices-sculptures, that allow participatory actions, in some cases, thus proposing a fantastic solution to real-world conditions, where machines that both fascinate and contribute to the development of society, but which can also cause alienation and malaise. The maquinices would be artistic answers the questions so pertinent to this time that we live, where the desperate consumption, waste and disrespect to the environment can have catastrophic results, however, solutions are emerging, maquinices seek to insert themselves as a source of reflection and awareness in this conjuncture.